Intelligent control of autonomous robots - Yang, Dong Xu (2009)
There is significant interest in autonomous vehicles – vehicles that are capable of intelligent motion and action without requiring either a guide to follow or teleoperator control. Potential applications of autonomous vehicles are many including reconnaissance/exploratory vehicles for space, undersea, land, and air environments; remote repair and maintenance; materials handling systems for the office and factory; and even intelligent wheelchairs for the handicapped. The earliest mobile robots began with Walter’s tortoise in 1950. Nearly two decades after Walter’s pioneer work, Stanford Research Institute began work on Shakey the robot in 1969. Shakey was a three wheeled robot, equipped with a camera, rang finder and other sensors. Numerous wheeled robots were developed in the 1970s, including various rovers for planetary exploration by the NASA Jet Propulsion Laboratory (JPL). Today the most common research robots are small wheeled vehicles.